Size Dependence of Doping by a Vacancy Formation Reaction in Copper Sulfide Nanocrystals. (19th July 2017) - Elimelech, Orian; Liu, Jing; Plonka, Anna M.; Frenkel, Anatoly I.; Banin, Uri
Abstract: Doping of nanocrystals (NCs) is a key, yet underexplored, approach for tuning of the electronic properties of semiconductors. An important route for doping of NCs is by vacancy formation. The size and concentration dependence of doping was studied in copper(I) sulfide (Cu2 S) NCs through a redox reaction with iodine molecules (I2 ), which formed vacancies accompanied by a localized surface plasmon response. X‐ray spectroscopy and diffraction reveal transformation from Cu2 S to Cu‐depleted phases, along with CuI formation. Greater reaction efficiency was observed for larger NCs. This behavior is attributed to interplay of the vacancy formation energy, which decreases for smaller sized NCs, and the growth of CuI on the NC surface, which is favored on well‐defined facets of larger NCs. This doping process allows tuning of the plasmonic properties of a semiconductor across a wide range of plasmonic frequencies by varying the size of NCs and the concentration of iodine. Controlled vacancy doping of NCs may be used to tune and tailor semiconductors for use in optoelectronic applications.